circ‐TTC17 Promotes Esophagus Squamous Cell Carcinoma Cell Growth, Metastasis, and Inhibits Autophagy‐Mediated Radiosensitivity Through miR‐145‐5p/SIRT1 Axis - Ying Liu; Shengmin Lan; Zhihui Duan (Thoracic Cancer)
ABSTRACT Background Circular RNA (circRNA) plays a significant role in esophagus squamous cell carcinoma (ESCC) progression. Nevertheless, circ‐TTC17 roles in ESCC have not fully understood. Methods The levels of circ‐TTC17, miR‐145‐5p and sirtuin 1 (SIRT1) were determined using qRT‐PCR. ESCC cell functions were examined by CCK8 assay, flow cytometry, transwell assay and colony formation assay. The relative protein levels of autophagy marker and SIRT1 were determined by western blot (WB). The interactions among circ‐TTC17, miR‐145‐5p, and SIRT1 were verified by dual‐luciferase reporter assay and RIP assay. Results circ‐TTC17 was overexpressed and miR‐145‐5p was underexpressed in ESCC. circ‐TTC17 knockdown restrained ESCC cell proliferation and metastasis, while enhance apoptosis and autophagy‐mediated radiosensitivity. Circ‐TTC17 could sponge miR‐145‐5p, and its inhibitor reversed the inhibitory effect of circ‐TTC17 knockdown on ESCC cell progression. Additionally, SIRT1 was targeted by miR‐145‐5p, and SIRT1 overexpression abolished miR‐145‐5p‐mediated the suppressive effect on ESCC cell progression. Also, circ‐TTC17 interference reduced ESCC tumor growth via miR‐145‐5p/SIRT1 axis. Conclusion circ‐TTC17 promoted ESCC cell growth, metastasis and inhibited autophagy‐mediated radiosensitivity by miR‐145‐5p/SIRT1 axis.